2018
DOI: 10.1002/prca.201700101
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Proteome of Invasive Retinoblastoma: Differential Proteins and Biomarkers

Abstract: The present study, is the first comprehensive quantitative membrane proteomic atlas of the differentially regulated proteins in RB compared to the retina. LMNB1 and TFRC could be potential biomarkers for this childhood cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…In addition, the silencing of LMNB1 impaired tumorigenicity, tumor invasion, and cell proliferation in pancreatic cancer cells [36]. Additionally, the overexpression of LMNB1 was the biomarker indicating the occurrence of retinoblastomas and poor prognosis of colon cancers [35,37]. e relationship between LMNB1 and LUAD has not been observed previously and LMNB1 might be a promising predictive biomarker and molecular target.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, the silencing of LMNB1 impaired tumorigenicity, tumor invasion, and cell proliferation in pancreatic cancer cells [36]. Additionally, the overexpression of LMNB1 was the biomarker indicating the occurrence of retinoblastomas and poor prognosis of colon cancers [35,37]. e relationship between LMNB1 and LUAD has not been observed previously and LMNB1 might be a promising predictive biomarker and molecular target.…”
Section: Discussionmentioning
confidence: 90%
“…In this study, we analyzed the expression of B7H3 in primary retinoblastoma tissues by immunohistochemistry for two reasons. (i) Our earlier study on proteomics of RB revealed significant expression of B7H3 in primary RB tumor samples compared to normal retina 7 , and, (ii) Definitive role of B7H3 in immune evasion of tumor cells by inhibiting T cell functions.…”
Section: Discussionmentioning
confidence: 97%
“…We had earlier performed a membrane proteomics comparing primary retinoblastoma and retinal tissue 7 . While comparing their expression for immunotherapy molecules we found B7-H3 (CD276); one of the B7 family checkpoint molecule to be overexpressed in RB tumor compared to the retinal tissue.…”
mentioning
confidence: 99%
“…Three microarray, gene expression datasets (GSE24673, 14 GSE97508, 15 and GSE110811 16 ) were retrieved from the Gene Expression Omnibus (GEO) database (https://www. ncbi.nlm.nih.gov/geo/).…”
Section: Data Sourcesmentioning
confidence: 99%